A chaos-enhanced accelerated PSO algorithm in reliable tracking of mobile objects. (12th March 2022) - Teymori, Sahar; Babaei, Peyman
Object tracking in monitoring applications is one of the topics in Internet of Things (IoT) issues. Most important key challenges in object tracking have concentrated on energy consumption and service quality and reliability. In the proposed approach the good performance of the PSO algorithm in global optimisation, and its weakness in local optimisation, is combined with the chaos operator to overcome this flaw. The purpose of the present research is to improve energy consumption and service quality and increase system reliability in mobile object tracking in WSNs. The goal is also to improve the algorithm performance. According to the results of the simulations, the energy consumption in the proposed method has been improved due to the optimal selection of the cluster heads. Also, the proposed method is stable while improving the reliability and increasing the quality of sensor network services.